GREEN SYNTHESIS OF MANGANESE OXIDE NPS USING MICROTRICHIA PEROTITII DC PLANT EXTRACT: CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY - Bamigboye, Mercy O.; Danjuma, Friday (Science Journal of University of Zakho, 2024)
This study presents a green approach to synthesizing manganese oxide nanoparticles (NPs) utilizing Microtrichia perotitii DC plant leaf extracts as a chelating agent and manganese oxide (MnO2) as a precursor. The NPs underwent comprehensive characterization through UV-visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy, scanning electron microscopy, and thermogravimetric analysis. X-ray diffraction patterns indicated the synthesis of MnO NPs with an average crystallite size of 10.12 nm. Scanning electron microscope images depicted a needle-like shape with uniform distribution. Fourier transform infrared spectrophotometer analysis identified the strongest bond at 862.025 cm-1 corresponding to the stretching vibration mode of Mn-O NPs. Thermogravimetric analysis confirmed the thermal stability of the NPs. Furthermore, the synthesized NPs exhibited antimicrobial activity against B. Subtilis with a zone of inhibition measuring 25.625±3.01 mm.